The Influence of Social Intelligence and Motivation on The Work Productivity of Organization Members Association of Angkasa Pura II Employee Wives Association Through Organizational Commitment - Safitri, Ira; Pasaribu, Bomer; Samosir, Partogi Saoloan (Krisnadwipayana International Journal of Management Studies, 2024)
PERISWARA II is an organization whose members are the wives of Angkasa Pura II employees. This research aims to analyse the influence of intelligence and motivation on members' work productivity through organizational commitment. This research was conducted at a non-profit organization, namely the Angkasa Pura II Employee Wives Association Organization (Periswara II) with a sample of 100 respondents. The sampling technique uses a random sampling system. The data analysis method uses descriptive analysis and path analysis with the SPSS Version 25 system. The research results show that the total influence between social intelligence and motivation on members' work productivity through organizational commitment shows a coefficient value greater than the coefficient value of the direct influence. Organizational commitment can mediate social intelligence and motivation in influencing members' work productivity.